Identification and validation of a major quantitative trait locus for precise control of heading date in wheat (Triticum aestivum L.) - Jin-Kyung Cha; Hyeonjin Park; Seong-Gyu Jang; Changhyun Choi; Youngho Kwon; So-Myeong Lee; Yurim Kim; Byung Jun Jin; Jong-Hee Lee; Soon-Wook Kwon; Woo-Jae Kim (BMC Plant Biology)
Abstract Background Heading date (HD) is a crucial agronomic trait in wheat, significantly influencing both adaptation and yield. Despite having identical genotypes for the major heading genes Vrn-1 and Ppd-1, two Korean wheat cultivars, Jokyoung and Joongmo2008, exhibit substantial differences in heading date. However, the underlying genetic factors responsible for this variation remain unclear. To address this, we aimed to identify major quantitative trait loci (QTLs) associated with narrow-sense earliness under field conditions and develop a practical molecular marker for wheat breeding programs. Results A recombinant inbred line (RIL) population was developed from a cross between the late-heading Jokyoung and the early-heading Joongmo2008 using speed breeding systems. The RILs were genotyped using a 35 K SNP chip, and a genetic map was constructed. A stable QTL for HD (qDH-3A) was identified on chromosome 3A, with an average logarithm of the odds (LOD) score of 59.4, explaining 72.6% of the phenotypic variance in HD across three years of field phenotyping. This indicates the robustness of qDH-3 A across multiple environments. Additionally, a kompetitive allele-specific PCR (KASP) marker linked to qDH-3A was developed and validated. The marker showed significant genotypic differences and effectiveness across diverse genetic backgrounds, including 616 worldwide wheat accessions. Conclusions The successful application of the KASP marker in both the RIL population and broader genetic resources highlights its potential use for marker-assisted selection (MAS) in wheat breeding programs. This study provides valuable insights into the genetic basis of HD in wheat and offers practical tools for developing cultivars better adapted to specific environmental conditions.